If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -11)(x + 4) = 0 Reorder the terms: (-11 + 3x)(x + 4) = 0 Reorder the terms: (-11 + 3x)(4 + x) = 0 Multiply (-11 + 3x) * (4 + x) (-11(4 + x) + 3x * (4 + x)) = 0 ((4 * -11 + x * -11) + 3x * (4 + x)) = 0 ((-44 + -11x) + 3x * (4 + x)) = 0 (-44 + -11x + (4 * 3x + x * 3x)) = 0 (-44 + -11x + (12x + 3x2)) = 0 Combine like terms: -11x + 12x = 1x (-44 + 1x + 3x2) = 0 Solving -44 + 1x + 3x2 = 0 Solving for variable 'x'. Factor a trinomial. (-4 + -1x)(11 + -3x) = 0Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(11 + -3x)' equal to zero and attempt to solve: Simplifying 11 + -3x = 0 Solving 11 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -3x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -3x = 0 + -11 -3x = 0 + -11 Combine like terms: 0 + -11 = -11 -3x = -11 Divide each side by '-3'. x = 3.666666667 Simplifying x = 3.666666667Solution
x = {-4, 3.666666667}
| 40x+10-1=-5x+36+48x | | x+1+x*2=-8 | | 3x-8+5x=7 | | -27+1= | | x+1+x*2=-6 | | 7b^2-5b=0 | | -24+(-3)= | | y=0.5*-2+3 | | y=4x^3-6x^2+3 | | (8+z)(3z+1)=0 | | 4x^7v^3*2v^9*6x=0 | | y=6-2*-2 | | -6s=30 | | 6x+108=12x-12 | | y=6-2*2 | | 4x+4=x+1+x*2 | | 500x-340=30x-3677 | | 12-6s=30 | | 4s-2=-4+2s | | 3x-25x-x+45= | | 5x+3y=3000 | | 9000=92x(1.8)t | | y=-4*-2 | | 2ab+6bc= | | 2+(-3)+(-18)= | | (x^2-6)-(x-4)= | | 45=2v+9 | | 2f+32=94-38 | | 14.5=-16a-4(-3a-4) | | 10x^2-5xy=0 | | -14x+49=-5x+55-7x | | 3y+15=15 |